ALISHER NAVOI'S ROLE IN THE FORMATION OF THE UZBEK LITERARY LANGUAGE - Egamova Shahida; Sukhanberdiyeva Sitora (Galaxy International Interdisciplinary Research Journal, 2022)
The present article talks about the role of the great thinker Alisher Navoi in the formation, development and evolution of the Uzbek language.